APPLICATION OF SPATIAL STRUCTURES IN BRIDGES DECK - Taghizadeh, Mohammad Hossein; Behravesh, Alaeddin (Civil Engineering Journal, 2015)
Spatial structure is a truss-like, lightweight and rigid structure with a regular geometric form. Usually from these structures is used in covering of long-span roofs. But these structures due to the lightness, ease and expedite of implementation are a suitable replacement for bridge deck. However steel and concrete is commonly used to build bridge deck, but heavy weight of steel and concrete decks and impossibility of making them as long-span bridge deck is caused engineers to thinks about new material that besides lightness and ease of implementation, provide an acceptable resistance against applied loads including both dead load and dynamic load caused by the passage of motor vehicles. Therefore, the purpose of this paper is design and analysis bridge deck that?s made of double-layer spatial frames compared with steel and concrete deck. Then allowable deflections due to dead and live loads, weight of bridge in any model and also economic and environmental aspects of this idea is checked. As a result, it can be said that the use of spatial structures in bridge deck is lead to build bridge with long spans, reducing the material and consequently reducing the structural weight and economic savings. For geometric shape of the spatial structure bridge is used of Formian 2.0 software and for analysis of bridges is used of SAP2000 with finite element method (FEM).